Analisis Pengaruh Disiplin Kerja, Kemampuan Kerja Dan Budaya Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Perumahan Kawasan Permukiman Dan Pertanahan Kabupaten Alor - Manilau, Yuli Amelia; Gorang, Alvonso Fanisius; Hermayanti, Hermayanti; Peny, Theresia Lounggina Luisa (Peneliti.net, 2023)
Thesis title analysis of the influence of work discipline, work ability and work culture on employee performance at the housing settlement and land areas office of Alor Regency. This thesis examines the performance of an influential employee at the Alor District Residential Housing Office. The discussion of this thesis is intended to find out whether employee performance has a significant effect on work discipline, work ability and work culture at the housing agency office, settlement areas and land affairs Alor Regency. Employee performance is an absolute requirement that must be met in order to achieve company goals. Improving employee performance must be carried out by all components whitin the company. However, so far the employees of the housing, settlement and land areas office of Alor Regency in carrying out their duties have not paid attention to optimal performance so that it has an impact on achieving company goals. For this reason, it is necessary to pay attention to the factors of work discipline, work ability and work culture. In this study, the authors collected data using three methods, firstly the observation technique by conducting direct research observations of environmental conditions or research objects. The second is direct interviews eith the head of the service and other respondents. The three researchers also used library research by reading journals, final thesis and also profiles at the research office. The result of the study concluded that (1) Work Discipline has a positive and significant effect on the performance of employees at the housing and Land Affairs Office of Alor Regency. (2) Work Capability has a major effect on the performance of employees in the Housing and Settlement Area Housing Office of Alor Regency. (3) Work Culture has a direct effect on employee performance at the Alor District Housing and Land Affairs Office. (4) Performance has a simultaneous influence on employee performance at the Alor District Housing and Land Affairs Office.